Extreme poverty in Mexico: A policy proposal - Levy, Santiago (Estudios Económicos de El Colegio de México, 1991)
This paper: One, pulls together the implications of recent research on poverty indices, nutrition, fertility, incentives and related topics for the design of poverty alleviation programs. Two, measures the magnitude and regional composition of extreme poverty. And three, makes a concrete policy proposal to deal with extreme poverty.